Green Macroprudential Banking Stability Framework : A Global Transmission Mechanism Of Sustainable Finance - Wahyu Indah Sari; Sirojuzilam Hasyim; M. Syafii (DAS Institute, 2026)
The increasing exposure of the financial system to climate-related risks has encouraged the evolution of macroprudential policy toward sustainability-oriented frameworks. This study develops the Green Macroprudential Banking Stability Framework (GMBSF) as an integrated analytical model explaining how sustainable finance instruments influence banking system resilience. Unlike conventional approaches that treat green finance as a complementary policy, this research positions it as a core macroprudential transmission channel affecting systemic stability. The study employs a panel dynamic approach using multi-institution banking data over the 2015–2024 period to examine both short-run adjustments and long-run equilibrium relationships between green financing, Environmental, Social, and Governance (ESG) performance, and banking stability. Stability is proxied by the Z-Score, while capital adequacy, profitability, credit risk, and institutional size are incorporated as control variables. The empirical findings indicate that sustainable finance exposure and stronger ESG governance significantly enhance banking stability by improving risk absorption capacity, strengthening capital buffers, and reducing credit volatility. Conversely, higher non-performing loans weaken systemic resilience. The results support the argument that green finance functions as a macroprudential shock absorber within climate-sensitive financial systems. This study contributes theoretically by introducing a globally applicable green macroprudential framework that integrates sustainability indicators into systemic risk management architecture. The proposed GMBSF provides strategic implications for central banks and financial regulators in designing climate-responsive macroprudential policies to maintain financial stability during the transition toward a low-carbon economy.